2016
DOI: 10.1590/0001-3765201620140605
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific variation in leaf pigments and nutrients of five tree species from a subtropical forest in southern Brazil

Abstract: The purpose of this study was to analyze the seasonal variation in the nutrient and pigment content of leaves from fi ve tree species -of which three are perennial (Cupania vernalis, Matayba elaeagnoides and Nectandra lanceolata) and two are deciduous (Cedrela fi ssilis and Jacaranda micrantha) -in an ecotone between a Deciduous Seasonal Forest and a Mixed Ombrophilous Forest in the state of Santa Catarina, Brazil. Leaf samples were collected in the four seasons of the year to determine the content of macronut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The results indicate that seasonal and climatic variations play a key role in determining foliar nutrient and pigment content. Photosynthetic pigments are indicators of the level of plant acclimation to the environment, and for many species, there is a consistent relationship between pigment content and environmental variables (Bündchen et al, 2016). According to our results, B. microphylla can quickly acclimate to changes of light, nutrient input, and seasonal climate variations by shifting the foliar pigment content.…”
Section: Influence Of Seasonal Climatic Variabilitysupporting
confidence: 61%
“…The results indicate that seasonal and climatic variations play a key role in determining foliar nutrient and pigment content. Photosynthetic pigments are indicators of the level of plant acclimation to the environment, and for many species, there is a consistent relationship between pigment content and environmental variables (Bündchen et al, 2016). According to our results, B. microphylla can quickly acclimate to changes of light, nutrient input, and seasonal climate variations by shifting the foliar pigment content.…”
Section: Influence Of Seasonal Climatic Variabilitysupporting
confidence: 61%
“…High interspecific variation has been also reported for carotenoids (e.g. Asner et al, 2009;Bündchen et al, 2016). In turn, intraspecific variation has been also reported for leaf pigments (e.g.…”
Section: Genetic Variation Of N Alpina Pigment Contentmentioning
confidence: 91%
“…Sampling of all individuals was conducted from March to early May 2023, before the onset of spring in Cuba. For each individual, 3 leaves were selected (Gillies et al, 1999;Curtu et al, 2007;Enescu et al, 2013;Bündchen et al, 2015;Apostol et al, 2017;Des et al, 2020;Olvera Moreno et al, 2022) from the eastern side of the tree, to avoid possible errors in the parameters evaluated based on the development morphological and photosynthetic capacity of the leaf. Since these species have compound leaves with more than 4 to 5 pairs of leaflets per compound leaf, this number of selections was considered representative and sufficient, and a total of 771 leaves were sampled.…”
Section: Study Sitementioning
confidence: 99%
“…Furthermore Bündchen et al (2015) investigated in a subtropical forest in southern Brazil the leaf structure of woody species in the canopy and understory, where they reported that Cedrela fissilis, Cupania vernalis, Matayba elaeagnoides and Nectandra lanceolata had lower specific leaf area, but higher density of stomata and thickness of palisade parenchyma. While the rest of the evaluated species, Allophylus guaraniticus, Lantana brasiliensis and Gymnanthes concolor, presented a greater thickness of the spongy parenchyma and relative percentage of intercellular spaces in the spongy parenchyma.…”
Section: Morphological Descriptors Analysismentioning
confidence: 99%